Seamless integration of computer-aided geometric modeling and acoustic simulation: Isogeometric boundary element methods based on Catmull-Clark subdivision surfaces. (November 2020) - Chen, L.L.; Zhang, Y.; Lian, H.; Atroshchenko, E.; Ding, C.; Bordas, S.P.A.
Highlights: Simulates acoustics problems with isogeometric boundary element methods. Integrates computer simulation with computer-aided geometric design. Constructs complicated geometries with Catmul-Clark subdivision surfaces. Retains geometric accuracy and removes cumbersome preprocessing procedures. Abstract: Isogeometric boundary element method is a computer simulation algorithm that can directly utilize the data of a geometric model represented by its surface. Catmull-Clark subdivision surfaces are a widely used technique in 3D computer graphics to construct complicated geometries. In the present work, we combine Catmull-Clark subdivision surfaces with isogeometric boundary element method to simulate acoustic propagation in semi-infinite domains. The present method can produce fast and high fidelity results, due to its strength of seamless integration of computer-aided geometric modeling and numerical simulation. The feasibility of the method is demonstrated by several acoustic scattering problems, including the one with analytical solutions and the examples with complicated geometries.